2013
DOI: 10.1111/jvim.12127
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic Review of Nonsteroidal Anti‐Inflammatory Drug‐Induced Adverse Effects in Dogs

Abstract: The aim of this systematic review was to identify, assess, and critically evaluate the quality of evidence of nonsteroidal anti-inflammatory drug (NSAID)-induced adverse effects in dogs. Original prospective studies published in peer-reviewed journals in English (1990English ( -2012 that reported data on the safety of NSAIDs administration in dogs were searched. For each study, design type (I, II, III, or IV) and assessment of quality (+, Ø, À) were rated. For each drug, quantity and consistency rating (***, *… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
179
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(187 citation statements)
references
References 80 publications
3
179
0
5
Order By: Relevance
“…Unfortunately, chronic use of some of these NSAIDS has been linked to adverse events, including reduced appetite, vomiting, gastrointestinal bleeding and hepatic and renal dysfunction [32,36,[38][39][40][41][42]. In a most recent placebo-controlled blinded prospective study, Monteiro-Steagall et al [37] reported that the incidence of adverse effects was statistically insignificant between treated and control dogs. Due to these concerns, dog owners and veterinarians have considered managing OA associated inflammation and pain in canine patients with nutraceuticals, herbs and other disease modifying agents which have minimal or no side effects [43].…”
Section: Pain Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, chronic use of some of these NSAIDS has been linked to adverse events, including reduced appetite, vomiting, gastrointestinal bleeding and hepatic and renal dysfunction [32,36,[38][39][40][41][42]. In a most recent placebo-controlled blinded prospective study, Monteiro-Steagall et al [37] reported that the incidence of adverse effects was statistically insignificant between treated and control dogs. Due to these concerns, dog owners and veterinarians have considered managing OA associated inflammation and pain in canine patients with nutraceuticals, herbs and other disease modifying agents which have minimal or no side effects [43].…”
Section: Pain Measurementmentioning
confidence: 99%
“…Pain after physical exertion, on a disease modifying agents and physical therapy with acupuncture have been used [19][20][21][22][23][31][32][33][34][35]. In the recent past, to manage OA in canine patients, most veterinarians have commonly used cyclooxygenase (COX) inhibiting non-steroidal anti-inflammatory drugs (NSAIDS), such as deracoxib, etodolac, carprofen, firocoxib, ketoprofen, meloxicam, rofecoxib, tepoxalin and others [36,37]. Unfortunately, chronic use of some of these NSAIDS has been linked to adverse events, including reduced appetite, vomiting, gastrointestinal bleeding and hepatic and renal dysfunction [32,36,[38][39][40][41][42].…”
Section: Pain Measurementmentioning
confidence: 99%
“…В систематическом обзоре [4] указывается, что частота побочных эффектов, связан-ных с поражением слизистой желудочно-кишечного тракта при приеме карпрофена составляет до 3,8%, а ча-стота возникновения гепатопатий (по мониторингу сы-вороточной активности печеночных ферментов) -0,05%. MacPhail C.M.…”
unclassified
“…In this regard, systemic NSAIDs may be indicated in cases of infectious uveitis or in patients with diabetes mellitus (COLITZ, 2005). Cyclooxygenase-2 (COX) selective NSAIDs are able to improve signs of inflammation and pain, minimizing the occurrence of adverse effects, such as gastrointestinal irritation, glomerular injury, and inhibition of platelet aggregation, usually associated to the suppression of COX-1 enzyme (MONTEIRO-STEAGALL et al, 2013). In cats, firocoxib guarantees the inhibition of 80 to 90% of COX-2, and less than 20% of COX-1 (MCCANN et al, 2005).…”
Section: Introductionmentioning
confidence: 99%